The Transformation of “Teh Ong”: Turning a Traditional Drink with Various Flavor Variants into a Superior Product in Banjar Lantangidung, Sukawati - Ni Luh Putu Putri, Setianingsih; Sudiarta, I Wayan; Rustini, Ni Made; Pratiwi, , Ni Luh Putu Yumi Mega; Jelita, Ni Putu Ayu Bunga; Indra, I Kadek (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
This community service program, "Teh Ong” was implemented in Banjar Lantangidung, Sukawati, to elevate the traditional beverage into a superior product. Teh Ong, a local beverage with various ginger and honey flavors, was previously managed without a professional approach. The program focused on providing comprehensive training to the local community, covering aspects of product and production management. Partners were taught to standardize production processes to maintain consistent quality and explore new, marketable flavor combinations. The program also focused on improving packaging, marketing, and product legality. This training enabled the community to design more attractive packaging and develop effective marketing strategies. Overall, the program has had a significant positive impact. Residents of Banjar Lantangidung have gained increased knowledge and skills in professionally managing Teh Ong. This has positioned Teh Ong not only as a local culinary heritage but also as a product with significant potential to boost the local economy. Contribution to Sustainable Development Goals (SDGs):SDG 8: Decent Work and Economic GrowthSDG 12: Responsible Consumption and ProductionSDG 17: Partnerships for the Goals